The Effect of Compensation and Motivation on Employee Performance: Study on Employees of Bank Jabar Banten Syariah Bandung City Branch - Lilis Sulastri (GoAcademica Research & Publishing, 2021)
To assess the impact of remuneration and work incentive indicators on employee performance at Bank Jabar Banten Syariah Bandung. Applicant's name: The saturated sample method was used to choose 50 Bank Jabar Banten Syariah Bandung workers. Data analysis utilizing various linear approaches. Using the SPSS 26 program. The results showed that the two variables evaluated had a favorable effect in part. Compensation (X1) has a t count > t table of 4.644 > 1.678, with a significance of 0.000< 0.05. And a 0.546 coefficient. Motivation (X2) has a t count > t table of 4.901 > 1.678 and a significance of 0.000 < 0.05. And a 0.545 coefficient. Employee performance is affected by both salary and motivation at Bank Jabar Banten Syariah Bandung. Using F count and F table, the result is 10.322 > 3.20. Compensation (X1) and Motivation (X2) have significance values of 0.000 < 0.05. Overall, salary and motivation have a considerable impact on employee performance. The examination of the coefficient of determination yielded 63.7 percent. That is, compensation and motivation affect 63.7 percent of their performance. Variables not addressed in this study explain the remaining 36.3 percent.